2013
DOI: 10.1186/1476-4598-12-58
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa NfsB and nitro-CBI-DEI – a promising enzyme/prodrug combination for gene directed enzyme prodrug therapy

Abstract: BackgroundThe nitro-chloromethylbenzindoline prodrug nitro-CBI-DEI appears a promising candidate for the anti-cancer strategy gene-directed enzyme prodrug therapy, based on its ability to be converted to a highly cytotoxic cell-permeable derivative by the nitroreductase NfsB from Escherichia coli. However, relative to some other nitroaromatic prodrugs, nitro-CBI-DEI is a poor substrate for E. coli NfsB. To address this limitation we evaluated other nitroreductase candidates from E. coli and Pseudomonas aerugin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…In addition, they observed wild type and mutated version of other nitroreductase enzymes such as flavin reductase FRase I from Vibrio Fischeri are able to activate CB1954 and its analogues [106, 111]. In parallel, others have developed new generation of nitroaromatic prodrugs such as nitro-CBI-DEI and PR-104A which can be activated both by hypoxia and bacterial nitroreductases [112]. Under hypoxic conditions (e.g., tumor environment), these two compounds undergo a one-electron transfer reduction reaction by human endogenous oxidoreductases but in normal cells they rapidly get reoxidazed [110].…”
Section: Enzyme/prodrug Systems: From Bench To Bedmentioning
confidence: 99%
“…In addition, they observed wild type and mutated version of other nitroreductase enzymes such as flavin reductase FRase I from Vibrio Fischeri are able to activate CB1954 and its analogues [106, 111]. In parallel, others have developed new generation of nitroaromatic prodrugs such as nitro-CBI-DEI and PR-104A which can be activated both by hypoxia and bacterial nitroreductases [112]. Under hypoxic conditions (e.g., tumor environment), these two compounds undergo a one-electron transfer reduction reaction by human endogenous oxidoreductases but in normal cells they rapidly get reoxidazed [110].…”
Section: Enzyme/prodrug Systems: From Bench To Bedmentioning
confidence: 99%
“…With the exception of NfsA (no hit sharing >20% identity across the full amino acid sequence), the best aligned predicted protein sequence from the P. aeruginosa genome was taken forward for further study (PA0949, 39% amino acid identity with WrbA; PA1204, 46% identity with ChrR; PA2580, 55% identity with MdaB; PA4975, 35% identity with NQO1; and PA5190, 25% identity with NfsB; Green et al, 2013). Primers for amplifying and cloning nfsB_ Pa, nqo1_Pa and chrR_Pa into pSX and pET28a + were as described in Prosser et al (2013), and for mdaB_Pa, wrbA_ Pa, and P. aeruginosa katA (PA4236) the following primer sets were used: mdaB_Fw (CCCCATATGAAAAACATTC TCCTGC), mdaB_Rv (CCCGTCGACTCAGCCG GCGC); wrbA_Fw (CCCCATATGTTGAGCAGTCCCTACATCCT), wrbA_Rv (CCCGTCGACTCAACTCCCCAGCTTGCCGG); and katA_Fw (CCCCATATGGAAGAGAAGACCCGCCT), katA_Rv (CCCGCGGCCGCTCAGTCCAGCTTCAGGCC GA) (restriction sites used for cloning are in bold).…”
Section: Identification and Cloning Of Kata And Quinone Oxidoreductasmentioning
confidence: 99%
“…In contrast paArsH and paMdaB have rates that are approximately 5 and 3 fold faster respectively. This is the first evidence of nitroreductase activity of these enzymes present in P. aeruginosa as a previous study [43] using an indirect readout showed no activity over background during overexpression of these enzymes in cancer cell lines.…”
Section: Nitrofurazone Reductionmentioning
confidence: 69%